Continuity and the «Godasos with a reputation of patriots: Lambayeque 1820-1823 - Figueroa Luna, Guillermo (2022)
We combine the study of published sources with archival manuscripts in order to analyze some contradictions between the landowner class, the peasants called «indians» and the plebs in the Independence movement of the Lambayeque region of Peru, from its antecedents until the years 1820 to 1823. The contradiction between the workers and the elite momentarily and partially struck the landed power, opening a fissure in the system of social oppression. But this could not be taken advantage of by the popular classes since they had neither a program, an organization, nor experienced leaders. Soon after that, the landowners regained the full power of their power. Some workers came to call the new rulers of Independence: «godasos (spaniards) with a reputation as patriots».